Development vectors for the NNSUACE campus - Gelfond, Anna; Lapshin, Andrei (project baikal, 2020)
The Nizhny Novgorod State University of Architecture and Civil Engineering (NNSUACE) campus is located in Zapochainie, a historical area in Nizhny Novgorod, so the issues of revitalization of the historico-architectural environment and those concerning the methods of architectural design are interwoven in the text. The symbiotic relationship between education, science and practice used as a principal tool for the training of architects at NNSUACE made it possible to envision the evolution of the university campus. The article presents the projects proposed by professional architects and students in response to the need to meet both practical and ideological challenges – to transform the university campus into a viable public space.